(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the clinical characteristics of pregnant women infected with COVID-19 treated at Ha Noi Obstetrics and Gynecology Hospital from December 2021 to April 2022. Materials and method: A retrospective cross-sectional study describing 1261 pregnant women diagnosed with COVID-19 with a gestational age of 22 weeks or more hospitalized for treatment at Ha Noi Obstetrics and Gynecology Hospital. Results: During the period from December 6, 2021, to April 30, 2022, Hanoi Obstetrics Hospital treated a total of 1,261 pregnant women for COVID-19. The average maternal age of these women was 29.6 years with a standard deviation of 5.1 years. Among the pregnant women treated, the majority had a mild form of the virus (88.7%), while 7.3% had a moderate form, and 4.0% had a severe form. The most common symptoms reported by pregnant women with Covid-19 were cough (57.3%), sore throat (40.2%), and nasal congestion (41.2%). In the severe group, it was observed that a higher number of vaccinations corresponded to a decrease in severity, with the severe form decreasing from 6.3% to 0%, showing a statistically significant difference (p=0.000 <0.05). Furthermore, the presence of diabetes was found to increase the severity of the disease in the severe and moderate groups, with a statistically significant difference (p=0.016 <0.05). Conclusion: Various factors, including gestational age, number of vaccinations, clinical symptoms and diabetes, can impact disease severity.